Ответ: 0
![image](https://tex.z-dn.net/?f=%7Cx%5E2+-5x%2B6%7C%3E+x%5E2+-5x%2B6%0A%5C%5C%5C%0A+%5Cleft+%5C%7B+%7B%7Bx%5E2+-5x%2B6%3E+x%5E2+-5x%2B6%7D+%5Catop+%7Bx%5E2+-5x%2B6%3C-+x%5E2+%2B5x-6%7D%7D+%5Cright.+%0A%5C%5C%5C%0A+%5Cleft+%5C%7B+%7B%7B0%3E0%7D+%5Catop+%7B2x%5E2+-10x%2B12%3C0%7D%7D+%5Cright.+%0A%5C%5C%5C%0Ax%5E2+-5x%2B6%3C0%0A%5C%5C%5C%0AD%3D25-24%3D1%0A%5C%5C%5C%0Ax_1%3D+%5Cfrac%7B5%2B1%7D%7B2%7D%3D3%0A%5C%5C%5C%0A+x_2%3D+%5Cfrac%7B5-1%7D%7B2%7D%3D2%0A%5C%5C%5C%0Ax%5Cin+%282%3B3%29)
x^2 -5x+6
\\\
\left \{ {{x^2 -5x+6> x^2 -5x+6} \atop {x^2 -5x+6<- x^2 +5x-6}} \right.
\\\
\left \{ {{0>0} \atop {2x^2 -10x+12<0}} \right.
\\\
x^2 -5x+6<0
\\\
D=25-24=1
\\\
x_1= \frac{5+1}{2}=3
\\\
x_2= \frac{5-1}{2}=2
\\\
x\in (2;3)" alt="|x^2 -5x+6|> x^2 -5x+6
\\\
\left \{ {{x^2 -5x+6> x^2 -5x+6} \atop {x^2 -5x+6<- x^2 +5x-6}} \right.
\\\
\left \{ {{0>0} \atop {2x^2 -10x+12<0}} \right.
\\\
x^2 -5x+6<0
\\\
D=25-24=1
\\\
x_1= \frac{5+1}{2}=3
\\\
x_2= \frac{5-1}{2}=2
\\\
x\in (2;3)" align="absmiddle" class="latex-formula">
Ответ: 2